The Role of Sign Language Avatars in Enhancing Educational Access and Public Services for the Deaf Community - Rajabani, Defitria Nur; Juhana, Agus (Titik Imaji, 2025)
In 2021, approximately 22.5 million people in Indonesia had disabilities, with hearing impairments being among the most prevalent. Access to education and information for the deaf community remains limited, particularly in rural areas. As a result, many deaf individuals rely on visual communication methods, such as sign language, which can be challenging for the general public to understand without specialized training. In situations where communication with non-sign language speakers is necessary, the deaf community often resorts to alternatives such as lip-reading, sign language interpreters, or assistive technology. Sign language avatars have emerged as a technological innovation aimed at bridging the information access gap for the deaf community. This study seeks to review the development of sign language avatars, assess their effectiveness in improving educational access and public services for the deaf, and highlight the importance of involving the deaf community in the development of such technologies. A literature review was conducted following the PRISMA 2020 approach, with data sourced from the Publish or Perish database. The findings suggest that advanced technologies such as artificial intelligence, 3D modeling, and augmented reality have significantly enhanced the delivery of sign language, facilitating more inclusive interactions. Avatars incorporating visual features such as facial expressions and smooth body movements improve communication comprehension by conveying emotions and contextual meaning. Sign language avatars not only boost learning motivation but also promote more effective communication between the deaf and the general public, particularly in inclusive education and public service contexts. This technology has substantial potential to bridge information access gaps and improve the quality of life for the deaf community in Indonesia, especially when developed with active involvement from the user community.